The Effect of Technopreneur Education and Entrepreneurship Motivation on Entrepreneurial Interest with Self Efficacy as an Intervening Variable - Widya Febriyanti; Bella Pricilia; Rusmewahni Rusmewahni; Kumala Vera Vera Dewi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of technopreneur education and entrepreneurial motivation on interest in entrepreneurship with self-efficacy as an intervening variable. This research uses a quantitative approach. The population in this study were 137 students from the Bina Karya Tebing Tinggi School of Economics who took part in technopreneur education. Sampling used purposive sampling. The results of this research show that technopreneur education has a positive effect on interest in entrepreneurship, entrepreneurial motivation has a positive effect on interest in entrepreneurship, Technopreneur education has a positive effect on self-efficacy, entrepreneurial motivation has a positive effect on self-efficacy, self-efficacy has a positive effect on interest in entrepreneurship, self-efficacy has a positive and significant effect in mediating the effect of technopreneur education on interest in entrepreneurship, Self-efficacy has a positive and significant effect on entrepreneurial motivation on entrepreneurial interest